High-resolution scanning electron microscopy for the analysis of 3D ultrastructure of clots in acute ischemic stroke - Mereuta, Oana Madalina (J Neurointerv Surg, 2020)
BACKGROUND: Characterization of acute ischemic stroke (AIS) clots has typically focused on two dimensional histological analysis of the thrombus. The three dimensional (3D) architecture and distribution of components within emboli have not been fully investigated. The aim of this study was to examine the composition and microstructure of AIS clots using histology and serial block-face scanning electron microscopy (SBFSEM). METHODS: As part of the multi-institutional STRIP registry, ten consecutive AIS emboli were collected from ten patients treated by mechanical thrombectomy. Histological and immunohistochemical analysis was performed to determine clot composition. SBFSEM was used to assess ultrastructural organization of clots and specific features of individual components. RESULTS: Quantification of Martius Scarlett Blue stain identified fibrin (44.4%) and red blood cells (RBC, 32.6%) as main components. Immunohistochemistry showed a mean platelet and von Willebrand content of 23.9% and 11.8%, respectively. The 3D organization of emboli varied greatly depending on the region analyzed. RBC-rich areas were composed of tightly packed RBC deformed into polyhedrocytes with scant fibrin fibers interwoven between cells. Regions with mixed composition showed thick fibrin fibers along with platelets, white blood cells and RBC clusters. Fibrin-rich areas contained dense fibrin masses with sparse RBC. In three cases, the fibrin formed a grid-like or a sponge-like pattern likely due to thrombolytic treatment. Segmentation showed that fibrin fibers were thinner and less densely packed in these cases. CONCLUSIONS: 3D-SEM provides novel and potentially clinically relevant information on clot components and ultrastructure which may help to inform thrombolytic treatment and medical device design.